PEDAGOGIC ISSUES FOR TEACHING BUSINESS ENGLISH - Vakoulenko, T.A. (Proceedings of National Aviation University (archive), 2005)
The article dwells upon pedagogical issues for teaching Business English. Considered are the peculiarities of BE syllabus, which depends on the learners’ needs; language proficiency and skills requirements for BE teachers, the balance of training time to be spent on input and output; feedback on learners’ performance, flexibility of the trainer etc.